2014
DOI: 10.1111/jocn.12734
|View full text |Cite
|
Sign up to set email alerts
|

To what extent is the work environment of staff related to person‐centred care? A cross‐sectional study of residential aged care

Abstract: Promoting a positive and supportive psychosocial climate and a work environment where staff experience balance between demands and control in their work, to enable person-centred care practice, seems to be important implications for managers and leaders in residential aged care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
84
2
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 32 publications
11
84
2
11
Order By: Relevance
“…The spontaneous narratives of the older persons list shortcommings in staff such as no education, no previous experience of caregiving and not being able to speak Swedish as reasons for this. This is confirmed by a Swedish study of staffs’ perceptions of person‐centred care in nursing homes (Sjögren, Lindkvist, Sandman, Zingmark, & Edvardsson, ) which found that lower levels of job strain, high levels of conscious stress, higher levels of staff satisfaction and supportive psychosocial climate for the staff were associated with person‐centred care. A reasonable explanation of the decrease in safety in the intervention group can therefore be shortage of staff leading to a high workload, high staff turnover and/or an insufficient leadership.…”
Section: Discussionsupporting
confidence: 55%
“…The spontaneous narratives of the older persons list shortcommings in staff such as no education, no previous experience of caregiving and not being able to speak Swedish as reasons for this. This is confirmed by a Swedish study of staffs’ perceptions of person‐centred care in nursing homes (Sjögren, Lindkvist, Sandman, Zingmark, & Edvardsson, ) which found that lower levels of job strain, high levels of conscious stress, higher levels of staff satisfaction and supportive psychosocial climate for the staff were associated with person‐centred care. A reasonable explanation of the decrease in safety in the intervention group can therefore be shortage of staff leading to a high workload, high staff turnover and/or an insufficient leadership.…”
Section: Discussionsupporting
confidence: 55%
“…A work situation that is too demanding can transform a previously patient‐focused professional into a self‐focused professional, as a survival strategy. Previous research has shown that to work with older patients in a person‐centred way, moral stress decreases (Sjögren, Lindkvist, Sandman, Zingmark, & Edvardsson, ) and job satisfaction increases (Ericson‐Lidman & Strandberg, ). However, working in a person‐centred manner presupposes a power shift from the professional to the patient, which is in line with our results where patient participation should be seen as an ongoing process, in a reciprocal collaboration, covering all encounters.…”
Section: Discussionmentioning
confidence: 99%
“…Backman et al, ). Previous national and international nursing home studies (Edvardsson, Petersson, Sjogren, Lindkvist, & Sandman, ; Martínez, Suárez‐Álvarez, Yanguas, & Muñiz, ; Rokstad, Engedal, Edvardsson, & Selbæk, ; Sjögren, Lindkvist, Sandman, Zingmark, & Edvardsson, ) that have used P‐CAT have shown person‐centred mean score between 45–49. Compared to these previous international PCC estimations, a mean score of 56 in this study's sample of nursing homes was considered as high.…”
Section: Methodsmentioning
confidence: 98%